PEER-ORIENTED INTERVENTION: A SOCIAL FACTOR OF LANGUAGE SHIFT IN ELEMENTARY SCHOOL STUDENTS - Ihda Rosdiana (PAROLE: Journal of Linguistics and Education, 2014)
This study aims at ascertaining the social factor causing the shifting of Bahasa Jawa Ngoko into Bahasa Indonesia among the elementary school students and confirming whether this phenomenon also occurs in all grades. The data were collected through observation and interview. Those data were analyzed using interactive analysis model (Milles & Huberman, 1994). There are two triangulations used in this research: source and method triangulations. Finally, the research found that peer-oriented intervention (Mrug et al,. 2001) functions as a social factor of language shift. However, this Javanese shift did not occur in the fifth grade students since they are from the same speech community.   Penelitian ini bertujuan untuk mengetahui faktor sosial yang menyebabkan pergeseran Bahasa Jawa Ngoko dalam Bahasa Indonesia di kalangan siswa sekolah dasar dan memastikan apakah fenomena ini juga terjadi di semua kelas. Data dikumpulkan melalui pengamatan dan wawancara. Selanjutnya, data tersebut dianalisis dengan menerapkan model analisis interaktif (Milles &Huberman, 1994). Selain itu, penelitian ini menggunakan triangulasi sumber dan metode. Penelitian ini menemukan bahwa peer-oriented intervention berfungsi sebagai faktor sosial pergeseran bahasa. Namun, pergeseran Bahasa Jawa Ngoko ke Bahasa Indonesia ini tidak terjadi pada siswa kelas lima karena mereka berasal dari komunitas bahasa yang sama.